QUALITY OF OIL USED TO FRY NILA FISH REPEATEDLY BASED ON FFA, SMOKE POINT, REFRACTION INDEX, AND VISCOSITY PARAMETERS - Budiyanto Budiyanto; Devi Silsia; Lukas Morasi Lumban Tobing (BPFP Faperta UNIB, 2015)
Oil is one of the important basic material in the process of frying and it is functioned as heat transfer media. During a process of frying, oil is experiencing quality declaining to be marked by forming free fatty acid and peroxides as the result of oxidation or triglyceride hydrolysis. This research aimed to determine the limit of usage and study on the quality change of oil used to fry nila fish repeatedly. Process of frying was done by applying two methods; with new oil added and with no oil added during the process of frying. Parameters observed were the free fatty acid (ffa), smoke point, refraction index, and viscocity. Result of the research showed that both method of frying could be repeated up to ten continues process of frying to have the oil quality within the standard limit of deterioration. At the tenth process of frying, for both method of frying, the ffas of the used oils were 0.5 % and 0.3 % that were lower then the standar ( 0.9132 %); the points of smoke were 200°C and 203.33°C compare to the standar (170°C); the viskositis were 15.29191 Cp and 15.07 Cp that were less than the standar (21.6 Cp); and the refraction indexes were 0.81 and 0.96 that were lower than the standar of oil deteriorated (1.46).Keywords: